Exploring Destination Uniqueness: Unraveling Revisit Intentions Through Enhanced Tourist Experiences - Auriza, Mohammad Zeylo; Setiawan Mandala Putra; Nirwan, Nirwan; Nugraha, Mohammad Ega (International Journal of Economics (IJEC), 2024)
This research aims to prove whether there is an influence between destination uniqueness on tourist experience and intention to visit again, the influence of tourist experience on intention to visit again, and prove whether tourist experience can mediate the relationship between destination uniqueness and intention to visit again. This research was conducted in Donggala Regency by focusing on Bonebula Beach. Sampling was carried out using a purposive sampling approach. The data that will be used to test the hypothesis is 120 respondents. The analytical equipment that will be used is structural equation modeling (SEM) using AMOS which can help researchers find and obtain the desired data. The research results show that the uniqueness of the destination influences tourists' experiences and also influences their intention to visit again. Other findings show that tourists' experiences have a positive influence on their intention to visit again. Research findings also show that tourist experience can positively mediate the relationship between destination uniqueness and revisit intention. Keywords: Destination Uniqueness; Tourist Experience; Revisit Intention; Tourism